XV. Yüzyılda Türk musikisi nazariyatı - Can, M. Cihat (My University, 2001)
XV. Yüzyıl Türk mûsikîsi tarihinde önemli bir dönemdir. Zeynü'l-Elhân, Matla' ve Muradnâme gibi ilk Türkçe müzik yazmaları bu dönemde yazılmıştır. XV. yüzyılda yazılmış olan müzik kitaplarında aralık hesaplamaları ve tel bölünmeleri gibi konular geniş yer tutmaktadır. Bu çalışmada XV. Yüzyıl Türk mûsikîsi nazariyâtında ses sistemleri konusu ele alınmıştır.

15th century is an important period in the history of Turkish music. The first Turkish writings of music such as Zeynü'l-Elhân, Matla' and Muradnâme were written in this period. The writings of music in the 15th century includes subjects such as the calculations of musical intervals and the divisions of strings on a large scale. In this study, the tonal system in Turkish music theory in the 15 th century was investigated.
Keywords: Dini Müzik; Müzik-dini Müzik